A282 EUS GUIDED FIDUCIAL PLACEMENT FOR PANCREATIC TUMORS AND TECHNICAL ISSUES IN ANTICIPATION OF STEREOTACTIC RADIATION THERAPY. (15th March 2019) - Samson, J; de Malet, A; Bou-Farah, R; Ducreux, M; Malka, D; Boige, V; Burtin, P
Abstract: Aims: Stereotactic radiotherapy of pancreatic tumors needs implantation of fiducial markers to help targetting the tumor. In this retrospective study, we share our experience with pancreatic fiducial EUS guided placement. We looked into its technical feasibility, innocuity and strategies for optimal fiducial distribution. Methods: From 2014 to 2017, 27 patients (22 with pancreatic adenocarcinoma and 5 with metastasis to the pancreas) underwent EUS pancreatic fiducial placement in our center. The same operator used a standard linear echoendoscope and a dedicated 22G EUS needle with 4 preloaded fiducials. Depending on radiotherapy equipment availability at the time of the treatment, 19 patients underwent conventional radiotherapy and 8 patients stereotactic radiotherapy. We retrospectively evaluated the number of markers delivered, their position, migration and adverse events. For patients being treated by stereotactic radiotherapy, the radiotherapy team evaluated markers tracking success by the radiotherapy device and positioning compared to the ideal fiducial geometry (defined as a distance of > 2 cm and < 7 cm, an angle greater than 15° and no collinearity between each markers). For a stereotactic treatment to be possible, at least 2 markers where to be tracked at all times during treatment and ideally 3 in order to restrict as much as possible the irradiated field. Results: Misplacement or immediate fiducial migration was noticed for 3 of the first 9 patients treated. Immediate marker placement was satisfactory in the last 18 patients. The radiotherapy device managed to track at least 2 markers in 7 out of the 8 patients who underwent stereotactic radiotherapy even though ideal fiducial geometry was never achieved. All patients had at least 2 markers less than 2 cm apart. No serious adverse event was noted. One patient reported abdominal pain for 48h after the procedure but pancreatic enzymes level remained normal. A few technical difficulties arose during the first fiducial placements. In one patient, the endoscope operating channel was punctured and needed repair. In another patient, the delivery kit needle was kinked by the endoscope elevator and we needed to use another one. Conclusions: Intrapancreatic fiducial placement can be achieved safely by means of EUS but, due to a learning curve, the delivery technique should be attempted by experienced endosonographers. Furthermore, fiducial geometry allowing efficient tracking is not simple and one should seek feedback from the radiotherapy team. Fluoroscopic guidance combined with EUS seems to facilitate placement. As soon as fiducial placement quality will allow optimal tracking, it will be possible to conduct a prospective study evaluating stereotactic radiotherapy in pancreatic tumor treatment. Fiducial tracking by the stereotactic radiotherapy device Funding Agencies: None